2018
DOI: 10.1038/s41419-018-0277-7
|View full text |Cite
|
Sign up to set email alerts
|

BRM270 inhibits cancer stem cell maintenance via microRNA regulation in chemoresistant A549 lung adenocarcinoma cells

Abstract: Chemotherapy is a standard treatment for non-small-cell lung cancer (NSCLC). However, the dose-limiting toxicity of drugs and the development of chemoresistance are major clinical challenges to successful management of NSCLC. Asian traditional medicine is gaining global attention as a non-toxic alternative to chemotherapy. BRM270 is an extract formulated from seven Asian medicinal plants that has been shown to inhibit tumor cell proliferation in diverse cancer types. We previously demonstrated that BRM270 supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…Clinical studies showed that the overexpression of IL-6 and Cox-2 contributes significantly to tumor growth [ 6 , 19 21 ] and blockades of IL-6 and Cox-2 signaling are potential chemotherapies [ 17 , 20 22 ]. Furthermore, our previous studies showed that BRM270, former version of KJS018A, enables suppressing tumor growth in lung adenocarcinoma [ 23 , 24 ]. Therefore, in this study we investigated inhibitory effects of KJS018A to hepatic tumor growth via xenografting SNU398 and HepG2 hepatic malignant cells in nude mice.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical studies showed that the overexpression of IL-6 and Cox-2 contributes significantly to tumor growth [ 6 , 19 21 ] and blockades of IL-6 and Cox-2 signaling are potential chemotherapies [ 17 , 20 22 ]. Furthermore, our previous studies showed that BRM270, former version of KJS018A, enables suppressing tumor growth in lung adenocarcinoma [ 23 , 24 ]. Therefore, in this study we investigated inhibitory effects of KJS018A to hepatic tumor growth via xenografting SNU398 and HepG2 hepatic malignant cells in nude mice.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that in the gefitinib-resistant lung cancer PC9-CSCs, expression of miR-128 was markedly suppressed as compared to non-CSCs and upregulation of miR-128 reverses the gefitinib resistance of the lung cancer stem cells by inhibiting the c-met/PI3K/AKT pathway [72]. In another study, it was found that BRM270, an extract from seven plants, triggers the expression of miR-128 in lung CSCs and sensitized chemoresistant A549 lung cancer cells by attenuating lung CSC traits via inhibition of the activation of VEGF/PI3K/AKT signaling pathways [70]. Downregulation of miR-218 in lung cancer cells has been shown to induce constitutive activation of STAT3, which is critically associated with oncogenesis.…”
Section: Lung Cancermentioning
confidence: 99%
“…MiRNA-215 DTL [59] miR-148a WNT, β-catenin [60] miR-199a/b Gsk3β, Wnt/β-catenin-ABCG2 [61] miR-196b-5p STAT3 [62] miRs-31 EphB2 and EphA2 [63] miR-27a Apaf-1/caspase-9 [64] miR-372/373 Nanog, Hedgehog, NFκB, MAPK/Erk, VDR Jak-STAT, TGF-beta, PI3K-Akt, MAPK. [65,66] miR-137 DCLK1 [67] miR-146a β-catenin [68] miR-195-5p STAT3, BIRC5, BCL2, BCL-XL, SOX2, CD133, RBPJ, Notch2 [62,69] Lung miR-128 AKT/ERK, p38, c-met/PI3K/AKT, VEGF/PI3K/AKT, IL-6-JAK-STAT3 [70][71][72][73] miR-181b Notch2 [74] miR-138 TGFβ [75] miR-5100 Rab6 [76] miR-214 c-MYC [76] miR-708-5p Wnt/β-catenin [77] miR-873 miR-125a-3p…”
Section: Role Of Mirna and Oncogenic Signaling Pathways In Human Cancmentioning
confidence: 99%
“…Lung cancer is the most common type of malignancy and leading cause of cancer-related mortality in the world [ 59 ]. Small cell lung carcinoma (SCLC) and non-small cell lung carcinoma (NSCLC) are the two main histological types of lung cancers [ 60 ].…”
Section: Jnk Activation Is Induced By Aberrant Prx II Expression Imentioning
confidence: 99%